1969
DOI: 10.1037/h0028160
|View full text |Cite
|
Sign up to set email alerts
|

Posterior neodecortication in the rat: Age at operation and experience.

Abstract: Rats were subjected to visual-cortex damage either at 1 day of age or in adulthood and their ability to utilize pattern cues was assessed. No age effect was obtained. This was true for Ss with all or part of visual cortex removed and for Ss maintained postoperatively in visually rich, poor, or ordinary lab environments. The study did demonstrate, however, that Ss with visualcortex damage tend to use luminous flux cues while normal SB tend to use pattern cues in performing a brightness discrimination task, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

1970
1970
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 12 publications
1
17
1
Order By: Relevance
“…When the rats were trained by the classical procedure, our results were in accordance with those of numerous previous experiments (Bauer & Hughes, 1970;Bland & Cooper, 1969;Braun et aI., 1970;Lashley, 1931;Spear & Barbas, 1975;Thompson, 1969); they showed that rats after one-step damage to the visual cortex fail to relearn the H-V task. In general, our results in the brightness (B-W) and pattern (H-V) discrimination tasks using the classical training procedure in normal, unilateral, and bilateral (serially or simultaneously lesioned) rats replicated results of previous studies (Barbas & Spear, 1976;Bauer & Cooper, 1964;Bland & Cooper, 1969;Braun et al, 1970;Dru et aI., 1975aDru et aI., , 1975bGlendenning, 1972;Hamilton & Trichler, 1968;Lashley, 1931Lashley, , 1935Lashley, , 1937Le Vere & Morlock, 1973;Meyer et aI., 1966;Petrinovich & Bliss, 1966;Petrinovich & Carew, 1969;Scheff et aI., 1977;Spear & Barbas, 1975;Thompson, 1960Thompson, , 1969.…”
Section: Discussionsupporting
confidence: 81%
“…When the rats were trained by the classical procedure, our results were in accordance with those of numerous previous experiments (Bauer & Hughes, 1970;Bland & Cooper, 1969;Braun et aI., 1970;Lashley, 1931;Spear & Barbas, 1975;Thompson, 1969); they showed that rats after one-step damage to the visual cortex fail to relearn the H-V task. In general, our results in the brightness (B-W) and pattern (H-V) discrimination tasks using the classical training procedure in normal, unilateral, and bilateral (serially or simultaneously lesioned) rats replicated results of previous studies (Barbas & Spear, 1976;Bauer & Cooper, 1964;Bland & Cooper, 1969;Braun et al, 1970;Dru et aI., 1975aDru et aI., , 1975bGlendenning, 1972;Hamilton & Trichler, 1968;Lashley, 1931Lashley, , 1935Lashley, , 1937Le Vere & Morlock, 1973;Meyer et aI., 1966;Petrinovich & Bliss, 1966;Petrinovich & Carew, 1969;Scheff et aI., 1977;Spear & Barbas, 1975;Thompson, 1960Thompson, , 1969.…”
Section: Discussionsupporting
confidence: 81%
“…This sparing of cells might suggest that geniculate projections to cortex outside the marginal gyrus [in the normal cat: Glickstein et al, 1967;Garey and Powell, 1967;Wilson and Cragg, 1967] may be responsible for the sparing of visual function. Such an escape of pattern vision after lesions of area 17 has not been found for rats operated on the 22nd day [Tsang, 1937] or on the 1st day [Bland and Cooper, 1969], nor has it been found for object discrimina tion by baboons operated at age 1, 3 or 10 months [Jalagonia et al, 1967]; in these species there has been no clear evidence of lateral-genicu late projections to neocortex outside of area 17.…”
Section: Neonatal V? Adult Lesions Of Visual Cortexmentioning
confidence: 99%
“…Examination of the earlier studies shows that when Hebb-Williams mazes were used, the rats with lesions were able to learn within a reasonable period of time relative to the control group (Hughes, 1965;Schwartz, 1964;Smith, 1959;Will & Rosenzweig, 197h;. In comparison, relatively little learning occurred among the animals with lesions in this experiment or among the brain damaged animals in 2 other studies, one dealing with pattern vision after striate cortex damage (Bland & Cooper, 1969) and the other assessing spatial reversal performance after septa1 insult (Donovick el al., 1973). In those cases, the tasks may have been too difficult for the animals with lesions, and they may have reverted to stereotyped behaviors (e.g., position habits).…”
Section: Fingermentioning
confidence: 81%